Cognitive Differences between Men and Women with HIV: A Systematic Review and Meta-Analysis. (21st August 2021) - Dreyer, Anna J; Munsami, Adele; Williams, Taryn; Andersen, Lena S; Nightingale, Sam; Gouse, Hetta; Joska, John; Thomas, Kevin G F
Abstract: Objective: Although many studies report that women with HIV (WWH) are more vulnerable to cognitive impairment than men with HIV (MWH), this trend is not described consistently in the literature. In this systematic review and meta-analysis, we investigated whether the weight of evidence supports the existence of a significant sex difference in cognitive functioning among people with HIV and, if so, whether specific domains are affected. Method: A systematic literature search retrieved 4, 062 unique articles published between January 2000 and June 2019. Eligibility criteria were that studies directly compared adult WWH and MWH using a neuropsychological test battery. After extensive screening, we included 11 studies in the systematic review ( N = 3, 333) and 6 in the meta-analysis ( N = 2, 852). Results: Six studies included in the systematic review found WWH performed significantly more poorly on measures of cognitive performance than MWH; the other five found no sex differences. Meta-analytic results indicated that WWH performed significantly more poorly than MWH in three cognitive domains (psychomotor coordination, visuospatial learning, and memory), but magnitudes of effect sizes were small ( d = −.16, −.43, and − .30, respectively). Analyses detected no sex differences in global cognitive functioning and in the other cognitive domains. Conclusions: Sex differences in cognitive performance are small, and sociodemographic and psychiatric characteristics of WWH and MWH differ between studies. Cognitive differences between WWH and MWH may be explained by sex-based variation in these characteristics, the impact of which seems to outweigh that of HIV-related clinical variables (e.g., CD4 count and viral load).